A critical role of the explorative relational capability to enhance business performance: Empirical study in the Indonesia fashion industry - Denny Bernardus; Murry Harmawan Saputra; Maichal Maichal; Elia Ardyan (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2022)
A recent study proposes the concept of explorative relational capability (ERC) and examines ERC's importance in improving business performance. This study used 218 respondents. The research respondents were owners or managers of SMEs in the furniture industry. The analysis used is structural equation modeling. After developing the concept of explorative relational capability, this study examines its effects on product innovation, advantages of new value creation, and business performance. The results show that ERC can improve product innovation, the advantages of new value creation, and business performance in the fashion industry. Other results show that ERC can mediate the gap between entrepreneurial orientation-business performance. This research contribution is aimed at a resource-based view (RBV). Companies must have resources that can provide new solutions, develop new perspectives, and create creative ideas to drive maximum business performance